Impact of recent COVID-19 infection on liver and kidney transplantation – a worldwide meta-analysis and systematic review - Pollmann, Nicola Sariye; Dondorf, Felix; Rauchfuß, Falk; Settmacher, Utz; Pollmann, Lukas; Selzner, Markus (Frontiers in Immunology, 2025)
IntroductionThe shortage of suitable donor organs represents an ongoing global challenge for organ transplantation. During the COVID-19 pandemic, the number of transplantable organs was especially limited. To date, the impact of recent coronavirus-19 (COVID-19) infection on liver and kidney transplant recipients has not been systematically analyzed, which is essential for the development of future transplant management. MethodsWe conducted a systematic review and meta-analysis to assess the clinical outcomes of recent COVID-19 infection in the donor (1) or the recipient (2). A total of 17 studies were considered for systematic review, seven of these were included for meta-analysis. ResultsTransplantation of COVID-19 positive donors did not result in an impaired graft survival for liver or kidney transplantation up to 180-days of follow up. Additionally, a positive COVID-19 donor status was not associated with decreased overall survival in kidney transplant recipients within 180 days of transplantation. Nevertheless, an association was found with decreased overall survival in liver transplant recipients within the 180-day follow-up period.DiscussionHowever, the heterogeneity of studies investigating COVID-19 infection of the recipient did not allow a classification of the significance of COVID-19 positive recipients. Conclusively, a COVID-19 positive donor status should not be considered as an exclusive factor for declining a suitable liver or kidney for transplantation.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024562551.